PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS ICT PADA POKOK BAHASAN LINGKARAN UNTUK SISWA KELAS VIII SMP/MTS - Yoshe Larissa Ulfa; Putri Yuanita; Yenita Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this study is the lack of ICT-based learning media especially on geometry in the topic of circle. The topic of circle has potency to be developed visually by using a computer device to facilitate students to understand this topic. This study used Borg and Gall’s model that was modified by Sugiyono. The aim of this study is to develop valid and practical ICT-based media for learning mathematics to facilitate the 8th grade junior high school students to understand the topic of circle. The subjects were 35 students at 8th grade Junior High School 20 Pekanbaru. The instruments used were a questionnaire sheet for content validation, media validation and student responses. The questionnaires sheets were analyzed quantitatively and qualitatively. The analyzed data and discussion showed that ICT-based media for learning mathematics is valid with an average score of 3.16 by content validator and 2.85 by media validator. This media is also qualified and practical with an average of student responses was 0.98 on a small group test and 0.93 in the big group.Key Word : Instructional Media, ICT-based Media, Learning Mathematics.